2019
DOI: 10.1037/pac0000369
|View full text |Cite
|
Sign up to set email alerts
|

Trauma of terror and displacement: A narrative analysis of mental health of women IDPS in KPK (Pakistan).

Abstract: The present study examined the posttraumatic effects of terrorism on women, internally displaced from Federally administered tribal areas of Pakistan (FATA). The sample comprised of 130 women temporarily placed in Jalozai camps in Khyber Pakhtunkhwa province of Pakistan. Posttraumatic stress disorder scale (PTSD) was used to assess the mental health of respondents. The results revealed that most women were experiencing PTSD symptoms and 41% met the criteria for overall diagnosis of PTSD. Findings further revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As a consequence of the ‘war on terror’, the Pakistani military launched its own war against extremists/terrorists inside the country in areas bordering Afghanistan (Khalid and Roy, 2016). Thousands of people were forced to leave their homes and settle in other areas as Internally Displaced Persons, or IDPs (Abbasi et al, 2020; Ehsan et al, 2019). Our participants indicated that covering this displacement was particularly traumatic for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the ‘war on terror’, the Pakistani military launched its own war against extremists/terrorists inside the country in areas bordering Afghanistan (Khalid and Roy, 2016). Thousands of people were forced to leave their homes and settle in other areas as Internally Displaced Persons, or IDPs (Abbasi et al, 2020; Ehsan et al, 2019). Our participants indicated that covering this displacement was particularly traumatic for them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, local journalists may accept the fact that they are facing a problem that is causing them distress, but they may not know how to deal with that issue or where to go for help. They may reach out to their friends, colleagues or family members to seek emotional support but since the issue is considered taboo and the literacy rate about mental health is very low in that cultural context (Bibi, 2018; Dawn, 2017; Ehsan et al, 2019), they may not be able to express their feelings or emotions openly or the people they are talking to may not be able to provide any help or guidance. This may lead to further distress and increase in the severity of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the meaning of conflict can be changing in the minds of perpetrators of aggression, unfortunately the consequences of such aggression for victims is all too real and in important respects continual. Two Brief Reports examine the psychological consequences of terror on Pakistani (Ehsan, Riaz, & Khalily, 2019) and Yezidi (Msall, 2019) victims.…”
mentioning
confidence: 99%